Model Pendidikan Multikultural - Junaidi, Junaidi (LPPPM STAI Darul Hikmah Bangkalan, 2018)
The theology subject taught at the school tends merely to reinforce the faith and its achievements to go to heaven without consciousness for having dialogue with other religions. These conditions make religious education very exclusive and intolerant. The Model of multicultural education as an alternative solution to reduce That exclusive and intolerant. Multicultural education can serve as a transformational process, not merely tolerance process; it is not just teaching about different cultures of various ethnic and religious group and supports the appreciation, comfort, cosmos, tolerance of other cultures